The Effect of the Proportion of Vermicompost Fertilizer in Planting Media on the Growth of Papaya (Carica papaya L.) Calina Cultivar - Aprilia Naumi, Sandra; Wijaya, Wijaya; Wahyuni, Siti (Jurnal Agrosci, 2024)
Papaya is in great demand by the public because of its sweet taste and abundant vitamin and mineral content. The problem is that in recent years papaya productivity has fluctuated due to poor soil structure and lack of nutrients in the soil, which results in poor seed growth and unqualified seedlings, so efforts need to be made to find the right type of planting media to support papaya nurseries, one of which is with vermicompost fertilizer. This experiment aims to determine the effect of the proportion of vermicompost fertilizer in the planting medium on the growth of china cultivar papaya seedlings. The research method used was a completely randomized design with six treatments consisting of K0 = 100% soil and 0% vermicompost fertilizer (control), K1 = 80% soil and 60% vermicompost fertilizer, K2 = 60% soil and 40% vermicompost fertilizer, K3 = 40% soil and 60% vermicompost fertilizer, K4 = 20% soil and 80% vermicompost fertilizer and K5 = 0% soil and 100% vermicompost fertilizer. The experimental results showed a significant effect on the proportion of vermicompost fertilizer on plant growth rate and root length of plants aged 15, 30, and 45 DAP, as well as root volume, stem diameter, plant height, number of leaves, fresh weight and dry weight of plants aged 30, 45 and 60 DAP but not significantly different from the observation of plant growth capacity aged 7 and 14 DAP.